Agri Business Incubation Centre at ICAR-NINFET - Roy, Alok Nath (Indian Farming, 2020)
India is one of the important suppliers of Agri-Business products including handicrafts items to the world market. The Indian Agri-Business industry is highly labour intensive farm and cottage based industry and decentralized, being spread not only in the eastern part, but all over the country in rural and urban areas. Numerous entrepreneurs /artisans are engaged in crafts working on full-time and part-time basis. The industry provides employment to over six million artisans, which include a large number of women and people belonging to the weaker sections of the society. In addition to the high potential for employment, the sector is economically important from the point of low capital investment, high ratio of value addition, and high potential for export and foreign exchange earnings for the country. Located in the gate way to the entire eastern India, West Bengal specially Kolkata and suburbs is considerably having great opportunity to create and extend business opportunity. Located in the transit place on the way to Bangladesh and Nepal, Kolkata is bordering with Jharkhand, Orissa, and Uttar Pradesh. Thus, people from various cultures gather over here for many purposes. From the angle of exporting the agri-business products including handicraft items to other countries also, the place has also been considered viable.